AN ANALYSIS OF DEIXIS EXISTED ON ARTICLES AT JAKARTA POST - Ramasari, Maria (Journal of Language and Literature, 2020)
The use of deixis on every language has different forms including English because of the various different context, such as grammatical rules and also background of culture or custom in society. This research is conducted to identify and analyze the forms of  Deixis existed on Articles at Jakarta Post as contextual information. Research method of analyzing data used was descriptive qualitative research. Human  instrument and text analysis are used as instruments of collecting data. Based on the data analyzed, it was found that pronoun of person deixis was most frequently used (existed) as second person deixis, third person deixis, possessive personal plural person deixis, and reflective personal person deixis that was used as reference to participant role of a referent for describing the speaker, the addressee and referent which are neither speaker nor addressee in written forms. In addition, the deixis with focus on time was also existed on Jakarta Post’s articles as the moment of utterance which is the coding time (the time of utterance conveyed by informants) and receiving time (the time of recovery of information by the hearer who got the information). The deixis of place that was existed on articles of Jakarta Post, was deictic reference to describe the current locations of informants indicated.